[Political game of chess]. - Gould, F. Carruthers (Francis Carruthers), 1844-1925 (Truth ?, 1886)
Scholarly notes may be added at a later date.
Truth Christmas Number. -Dec. 25. 1886.
1 print : b&w
Keywords: Caricatures; Cartoons; Great Britain -- Politics and government -- 1837-1901.; Chess